MAIN PROBLEMS OF TRANSLATION. - Shomurodova Dildora Anvarovna (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Annotation. This article explores the fundamental problems encountered in the process  of  translation.  It  highlights  the  key  linguistic  and  cultural  challenges  that translators  face,  including  lexical,  grammatical,  stylistic,  cultural,  and  pragmatic issues. Through relevant examples and theoretical insights, the paper emphasizes the importance  of  context,  cultural  awareness,  and  communicative  intent  in  achieving accurate  and  effective  translation.  The  discussion  aims  to  contribute  to  a  deeper understanding of translation as a complex act of cross-cultural communication rather than a simple linguistic operation.